2005
DOI: 10.1111/j.1365-2133.2004.06335.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin-infiltrating neutrophils following exposure to solar-simulated radiation could play an important role in photoageing of human skin

Abstract: Our study suggests that neutrophils participate in the process of photoageing of human skin as they infiltrate the skin and release enzymatically active elastase (neutrophil elastase), collagenase (MMP-1) and gelatinase (MMP-9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 14 publications
7
71
0
2
Order By: Relevance
“…It is known that UV-induced MMPs are secreted by diverse cells, including infiltrated inflammatory cells. 21,22 We found that the inflammatory infiltrates were significantly decreased after the PDT. Therefore, the net effects of the induction of TFG-b and reduction of the degrading enzymes from the inflammatory cells likely contributed to the decreased expression of MMPs after the ALA-PDT.…”
Section: Discussionmentioning
confidence: 79%
“…It is known that UV-induced MMPs are secreted by diverse cells, including infiltrated inflammatory cells. 21,22 We found that the inflammatory infiltrates were significantly decreased after the PDT. Therefore, the net effects of the induction of TFG-b and reduction of the degrading enzymes from the inflammatory cells likely contributed to the decreased expression of MMPs after the ALA-PDT.…”
Section: Discussionmentioning
confidence: 79%
“…The structural integrity of the ECM is compromised with the increase in the basal or induced levels of MMPs/elastase enzymes as well as their activity with aging or exposure to UV radiation. The ECM proteolytic enzymes (MMPs/elastases) are produced by epidermal keratinocytes, dermal fibroblasts, neutrophils and melanoma cells in the mediation of skin aging or cancer [3,[15][16][17][18]. P. leucotomos extract directly inhibits the activities of MMPs (MMP-1, 2, 3, 9) as well as the cellular expression of MMPs (MMP-1, 2) in nonirradiated or UV radiated dermal fibroblasts or epidermal keratinocytes [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of skin or skin-derived cells to UVR, for example, is known to upregulate the expression of many elastic fibre degrading enzymes, including MMP-2, -3, -9, -12 and -13 and the serine protease neutrophil elastase (Fisher et al 1996;Kim et al 2006;Rijken et al 2005;Saarialho-Kere et al 1999). ROS generation may mediate elastic fibre damage in skin either indirectly, via protease upregulation (Yaar and Gilchrest 2007), or directly via interaction with the sulphur containing amino acids methionine and cysteine (Haenold et al 2005).…”
Section: Cutaneousmentioning
confidence: 99%